Fishery by-products, Calanus finmarchicus and mesopelagic fish species as alernatives to fish meal and fish oil in feeds for Atlantic salmon (Salmo salar L) - Henriksen, Anastasia (Nord universitet, 2020)
Masteroppgave i havbruk og akvakultur - Nord universitet 2020